Photodynamic therapy (PDT) in early central lung cancer: a treatment option for patients ineligible for surgical resection. Issue 5 (7th November 2006) - Moghissi, Keyvan; Dixon, Kate; Thorpe, James Andrew Charles; Stringer, Mark; Oxtoby, Christopher
Abstract : Objectives: To review the Yorkshire Laser Centre experience with bronchoscopic photodynamic therapy (PDT) in early central lung cancer in subjects not eligible for surgery and to discuss diagnostic problems and the indications for PDT in such cases. Methods: Of 200 patients undergoing bronchoscopic PDT, 21 had early central lung cancer and were entered into a prospective study. Patients underwent standard investigations including white light bronchoscopy in all and autofluorescence bronchoscopy in 12 of the most recent cases. Indications for bronchoscopic PDT were recurrence/metachronous endobronchial lesions following previous treatment with curative intent in 10 patients (11 lesions), ineligibility for surgery because of poor cardiorespiratory function in 8 patients (9 lesions) and declined consent to operation in 3 patients. PDT consisted of intravenous administration of Photofrin 2 mg/kg followed by bronchoscopic illumination 24–48 h later. Results: 29 treatments were performed in 21 patients (23 lesions). There was no procedure-related or 30 day mortality. One patient developed mild skin photosensitivity. All patients expressed satisfaction with the treatment and had a complete response of variable duration. Six patients died at 3–103 months (mean 39.3), three of which were not as a result of cancer. Fifteen patients were alive at 12–82 months. Conclusion: Bronchoscopic PDT in early central lung cancer can achieve long disease-free survival and should be considered as a treatment option in those ineligible for resection. Autofluorescence bronchoscopy is a valuable complementary investigation for identification of synchronous lesions and accurate illumination in bronchoscopic PDT.